Jak wygląda polski dom? Adres kulturowy w polskiej literaturze współczesnej z perspektywy glottodydaktycznej = How does a Polish home look like? Cultural address in Polish contemporary literature from a glottodidactic perspective - Válková Maciejewska, Monika (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article aims to present the advantages of teaching Polish as a foreign/second language through cultural texts, especially contemporary literature (the study quotes excerpts from such books as "Bezmatek" ["No-mother"] by Mira Marcinów, "Rozdeptałem czarnego kota przez przypadek" ["I`ve trampled a black cat accidentely"] by Filip Zawada, "Prymityw. Epopeja narodowa" ["Primitive. National epic"] by Marcin Kołodziejczyk).
Keywords: glottodydaktyka polonistyczna; glottokulturoznawstwo; adres kulturowy; nauczanie języka polskiego jako obcego/drugiego; lingwakultura; Polish language glottodidactics; glottocultural studies; cultural address; teaching Polish as a foreign/second language; Polish language for foreigners; contemporary Polish literature